Mitigation of mycotoxin residues and activation of endogenous stem cells in broiler chickens using a toxin binder: Implications for meat safety and performance enhancement - Erma Safitri; Hery Purnobasuki; Tita Damayanti Lestari; Suzanita Utama; Rimayanti Rimayanti; Mirni Lamid; Mutmainah Wardatul Jannah; Siti Darodjah; Goo Jang; Mitsuhiro Takagi (Veterinary World)
Background and Aim: Mycotoxin contamination in poultry feed, particularly with aflatoxin B1 (AFB1) and ochratoxin A (OTA), poses significant threats to broiler health, meat quality, and consumer safety. Toxin binders are commonly used to mitigate these effects; however, their impact on endogenous stem cell activity and overall broiler performance remains underexplored. This study aimed to evaluate the efficacy of a commercial toxin binder in reducing AFB1 and OTA residues in broiler meat, inducing endogenous stem cell production, and improving growth and feed performance indices.